Formal total synthesis of macarpine via a Au(I)-catalyzed 6-endo-dig cycloisomerization strategy - Fu, Jiayue; Li, Bingbing; Zhou, Zefang; Cheng, Maosheng; Yang, Lu; Liu, Yongxiang (Beilstein Journal of Organic Chemistry, 2022)
The formal total synthesis of macarpine was accomplished by the construction of a naphthol intermediate in Ishikawa’s synthetic route with two different synthetic routes. The convergent synthetic strategies feature the utilization of Au(I)-catalyzed cycloisomerizations of a 1,5-enyne and alkynyl ketone substrates, which were prepared by Sonogashira coupling reactions.
Keywords: benzo[c]phenanthridine alkaloids; 1,5-enyne; formal total synthesis; gold catalysis; macarpine